Organizational adaptation to working from home in a crisis situation (COVID-19): the interaction between leaders’ openness and followers’ voice - Buzás, Barnabás; Faragó, Klára (Frontiers in Psychology, 2023)
Introduction We investigated the effect of time spent at home on employee voice behavior and leadership openness during Covid 19. According to DeRue’s adaptive leadership theory which offers an interactionist perspective to explain adaptive organizational behavior during an environmental crisis, we proposed that in the WFH’s (work from home) reduced and limited communication space, leaders, who need more feedback, will encourage employees to express their opinions and will show more willingness to listen to them. Meanwhile, employees will ask more questions and make more suggestions to alleviate uncertainty and misunderstanding. Methods Using an online questionnaire, a cross-sectional study (N = 424) has been carried out with employees working from home for a different amount of their working time during the pandemic. Data were analyzed using structural equation models (SEM) in which the effect of leadership openness on employee voice behavior was assessed through the mediation of affective commitment, psychological safety, and intrinsic motivation. Results The results showed that in the WFH situation, time spent in home office had a low but significant direct negative effect on promotive voice behavior. At the same time, leadership openness was growing with the amount of time spent at home. Leadership openness counteracted the negative effect of WFH on voice behavior: although leadership openness did not have a direct significant effect on voice behavior, it had a positive effect on psychological safety and work motivation which, in turn, influenced positively both promotive and prohibitive voice behavior. Employee’s voice, for its part, further augmented leadership openness. Discussion In our research we could demonstrate the contingent nature and the mutual influence patterns and feedback loops of leaders-employees exchange. In the WFH situation the openness of the leader is growing with the amount of time spent at home and with the amount of promotive voice manifested by the employee. In consent with DeRue social interactionist adaptive leadership theory, a mutually reinforcing process of leadership openness and employee voice could be demonstrated. We argue that leadership openness is a key factor to motivate employee voice behavior during WFH.